Revisiting Abhijñanaśākuntalam : love, lineage and language in Kālidāsa's nāṭaka - Sengupta, Saswati; Tandon, Deepika (Orient Blackswan, 2011)
Papers presented at a two-day international conference held at Dept. of English, Miranda House College, University of Delhi in 2010.